Penerapan Pola Asuh Ala Rasulullah SAW Dalam Mencegah Inner Child Negatif Pada Anak Di Khalilah Islamic Daycare: Studi Kajian Hadis - Annisa Mayunda; Zulkarnaen (Cendekia, 2024)
This study examines the application of the Prophet's parenting style at Khalilah Islamic Daycare in preventing negative inner child in children. This study bases its analysis on hadiths related to the protection and care of children. which describes how the Prophet gave love, attention, and tenderness in educating children. The inner child formed through childhood experiences can affect a person's behavior in the future, and the Prophet's parenting style is an ideal model in educating children to avoid psychological trauma The focus of this study is on methods and strategies taken from the Prophet Muhammad's traditions related to parenting, as well as their impact on children's psychological development. This research uses a qualitative approach with a case study method. Data were obtained through in-depth interviews with caregivers, direct observation at the daycare, and analysis of relevant hadiths. The results show that the application of the Prophet's parenting style, such as affection, good communication, and character education, can significantly prevent the formation of a negative inner child in children. Children raised with this parenting style show improvement in self-confidence and social interaction skills. This study makes a new contribution to the field of Islamic education by integrating hadith values into modern parenting practices. It also enriches the literature on preventing negative inner child from an Islamic perspective, offering solutions based on the teachings of the Prophet Muhammad.